Landschaftsarchäologie am DAI: Zur Einrichtung eines neuen Arbeitskreises - Teichmann, Michael (e-Forschungsberichte des DAI, 2023)
In 2014 a new working group focusing on landscape archaeology (Arbeitskreis „Landschaftsarchäologie am DAI“ – LAAD) was established at the German Archaeological Institute. Its aim is to stimulate the exchange and discussion of the methods and theories employed in landscape archaeology research, both within the Institute, as well as the wider scientific community. The group aims to hold semi-annual meetings as a forum for exchanging experiences, sharing knowledge, and defining common aims within the research agenda. Practical workshop sessions will also be held in order to help improve relevant skills. A further aim is to increase the awareness of the growing importance of landscape archaeology within, and potential contribution to, the wider archaeological discourse.